ANALISIS MINAT MASYARAKAT MEMILIH PEMBIAYAAN DI PNM MEKAR SYARIAH CABANG KRONJO KABUPATEN TANGERANG MENURUT PERSPEKTIF EKONOMI ISLAM - Afifah Nazla Sevina; Suryani Suryani; Ratu Humaemah (Wahana Islamika: Jurnal Studi Keislaman, 2022)
The purpose of this study is to find out the factors that influence public interest in choosing financing at PNM Mekar Syariah, Kronjo Branch, Tangerang Regency, according to the Islamic Economic Perspective. The method used in this research is descriptive qualitative research. The data was obtained using the triangulation technique of data sources, by combining data collection with observation techniques, structured interviews and documentation. The results of this study indicate that the public's view of financing at PNM Mekar Syariah Kronjo Branch, Tangerang Regency is very good and helps people who need capital to run their business. PNM Mekar Syariah Branch Kronjo Tangerang Regency in its financing system uses three contracts used sharia namely wadi'ah contracts, wakalah contracts and murabahah contracts. The factors that influence people's interest in choosing financing at PNM Mekar Syariah Branch Kronjo Tangerang Regency are the need factor, religiosity factor, social class factor and service quality. Keywords: Interests, community, financing, PNM Mekar Syariah